Impact of closed fishing season on supply, catch, price and the fisheries market chain. (April 2022) - Macusi, Edison D.; Morales, Ilah Dianne G.; Macusi, Erna S.; Pancho, Aijelyn; Digal, Larry N.
Abstract: This study assessed how the closed fishing season policy that was implemented in Davao Gulf through the joint administrative order (JAO-2014 series 02) of the Department of Agriculture (DA) and the Department of Interior and Local Government (DILG) impacted fish supply, catch, and price and described the roles of actors involved in the fisheries supply chain. Data collection included semi-structured questionnaires (N = 150) and validated using in-depth interviews (N = 80) in Tagum, Panabo, and Davao public markets. Secondary data were used to compare the catch, value of production, and consumer price index. Results showed that most of the actors in the chain were trained by family members, worked in the market because of better income (Php 5001–20, 000; U100–400) and majority of them approved the closed fishing season because of perceived fish stocks recovery (>90%). Analysis of catch data for the municipal fisheries showed an increase from 223 tons to 317 tons while the catch of commercial fisheries showed decline from 238 tons to 92 tons ( t (286) = 11.57, P < 0.001). Similarly, the value of production also increased for the municipal fisheries (up to Php 34 million) and a decline of value for the commercial fisheries (down to Php 9 million) ( t (286) = 10.76, P < 0.001). An increase in the consumer price index (CPI) was also recorded after the implementation of the closed fishing season e.g. Php 102 vs Php 113 ( t (382) = 6.52, P < 0.001). Our results strongly recommend the retention of closed fishing season complemented by other effort control measures such as boat and gear registration, mesh size regulation, establishment of marine sanctuaries, and livelihood provisions for affected fishers.